Employment policies in developing countries - Rasul Shams (Intereconomics, 1976)
The ILO World Conference on Employment was held in Geneva from June 4 to 17, 1976 and after long discussions adopted an action programme which provided for quite a number of measures designed to ensure full employment in developing countries until the year 2000. The problems posed by a policy of full employment in developing countries are indicated in the following article which demonstrates that a change in the inherited power structures is a major prerequisite for an effective policy of full employment.
Keywords: 330; Employment